Pengaruh Kepemimpinan dan Pelatihan terhadap Kinerja Prajurit dan Aparatur Sipil Negara Pada Dinas Administrasi Personel TNI Angkatan Udara (Disminpersau) - Albertus Irianto (Madani Connection, 2025)
The leadership problem currently faced by Disminpersau is the lack of coordination in implementing work programs, which causes misunderstandings, this often occurs and can certainly lead to a lack of direction in achieving goals. The performance of Soldiers and ASN is the result of work within the scope of their responsibilities, of course, referring to a formal and structured system that is used as an instrument to measure, assess, and influence work-related traits, control the behavior of Soldiers and ASN. The method used is a survey method using a questionnaire. The type of research that the author uses in this study is a type of correlation research, this correlation method is actually a continuation of the descriptive method. In the correlation method, the influence between the variables studied and explained, the influence sought is called correlation. So the correlation method to find the Influence between independent variables X1 and X2 with dependent variable Y. Based on the research, there is a simultaneous significant positive influence between Leadership (X1), Training (X2) on the Performance of Soldiers/ASN (Y) at Disminpersau, where h is 174.227> 3.15 and significant at 0.000